Physical abilities and their relationship to some physiological variables of the 100-meter freestyle swimmers for youth - Mohammed Farhan, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The science of sports training has laid a basic foundation for all sporting activities, and the link and interaction of the science of sports training with other sciences can be used to achieve the required achievement. Physical abilities are one of the main factors affecting the swimmer’s speed in traveling the distance and achieving the best time during races and competitions. The research aims to identify the level of some physical abilities and some functional variables for swimmers (100 meters) for youth, as well as the relationship between some physical abilities and some functional variables for swimmers (100 meters) for youth. The sample included the national team swimmers for the youth age group (15-17) After presenting, analyzing, and discussing the results, the most important conclusions were the presence of a significant relationship between some physical abilities and some functional variables of the swimmers (100 meters) for the youth. The most important recommendations were the need to pay attention to some physical abilities in general and some functional variables (number of heartbeat, stroke size, and cardiac output) for my swimmers (100 meters) for young people in particular.